2017
DOI: 10.3748/wjg.v23.i34.6242
|View full text |Cite
|
Sign up to set email alerts
|

Dihydromyricetin-mediated inhibition of the Notch1 pathway induces apoptosis in QGY7701 and HepG2 hepatoma cells

Abstract: AIMTo investigate whether Dihydromyricetin (DHM) inhibits cell proliferation and promotes apoptosis by downregulating Notch1 expression.METHODSThe correlation between Notch1 and Hes1 (a Notch1 target molecule) expression in hepatoma samples was confirmed by qRT-PCR. In addition, MTT assays, flow cytometry and TUNEL analysis showed that DHM possessed strong anti-tumor properties, evidenced not only by reduced cell proliferation but also by enhanced apoptosis in QGY7701 and HepG2 hepatocellular carcinoma (HCC) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 32 publications
0
17
1
Order By: Relevance
“…The results indicated that the concentration of DHM < 100 μM had no toxic effects on the ARPE‐19 cells (Figure B). Compared with the previous studies, DHM (100 μM) was shown to inhibit cell proliferation in the human hepatic cancer cells …”
Section: Resultscontrasting
confidence: 56%
See 3 more Smart Citations
“…The results indicated that the concentration of DHM < 100 μM had no toxic effects on the ARPE‐19 cells (Figure B). Compared with the previous studies, DHM (100 μM) was shown to inhibit cell proliferation in the human hepatic cancer cells …”
Section: Resultscontrasting
confidence: 56%
“…Relevant studies have indicated that DHM can induce cell apoptosis in hepatocellular carcinoma cells through inhibiting cell proliferation in a p53‐dependent manner . Furthermore, Hou et al indicated that DHM suppressed the phosphorylation of NF‐κB, p38, and JNK, but not ERK 1/2 in LPS‐stimulated macrophages .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Human Notch is a transmembrane receptor protein encoded by one of the Notch1-4 genes. The Notch pathway plays a central role in cell differentiation [30], proliferation [31,32], apoptosis [33], metastasis [34], and stem cell maintenance [35]. Knockdown of Notch1 is reported to decrease chemotherapy resistance in cancer [36,37], and Notch1 can increase the expression of MRP1 to promote cancer chemoresistance [38].…”
Section: Discussionmentioning
confidence: 99%